Negative dialectics - Adorno, Theodor W. (Routledge, 1983)
This is the first British paperback edition of this modern classic written by one of the towering intellectual of the twentieth century. Theodor Adorno (1903-69) was a leading member of the Frankfurt School. His books include The Jargon of Authenticity, Dialectic of Enlightenment (with Max Horkheimer), and Aesthetic Theory